KNICKPOINTS TRANSITÓRIOS E PERFIS RELÍQUIA EM AFLUENTES DOS RIOS TEJO E ZÊZERE (PORTUGAL): ESTIMAÇÃO DA INCISÃO FLUVIAL EM TROÇOS AFECTADOS POR SOERGUIMENTO DIFERENCIAL - Martins, António (2014)
ABSTRACT Several tributaries of the Tejo and Zêzere rivers show a graded relict profile in the most upstream reach and a rejuvenated profile in the lower reach. A major slope break in the long profile (knickpoint) separates both reaches. Extrapolation of the oldest graded relict profile downstream to the confluence allowed the incision amount to be quantified. Results reveal that the downcutting is higher in streams flowing in uplifted sectors of the Portuguese Central Range (PCR), reaching more than 400 m of fluvial incision. Streams that flow from the PCR to the adjacent Planation surface have intermediate incision values (up to 295 m), and the streams that flow on the Planation surface have lower values (reaching 190 to 220 m). Differences in the incision values result from differential uplift. The normalized steepness index suggests modern tectonic activity in the Sobreira Formosa fault, Sertã fault and Pracana fault. The bedrock lithology influences the erosion wave propagation (non linear nature) and that results in different knickzone morphologies.